2006
DOI: 10.1007/s00383-006-1796-3
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid intestinal perforation in children: a continuing scourge in a developing country

Abstract: Typhoid intestinal perforation is a principal cause of morbidity and mortality affecting both adults and children. This study aims to evaluate the pattern of typhoid intestinal perforation and outcome of its management in Nigerian children. The records of consecutive children managed for typhoid intestinal perforation at Juth, between 1996 and 2005 have been reviewed. There were 184 children (M:F = 1.04:1), with a mean of 5.8 years (range 4 to 15 years). More than a half (62.5%) of the patients were in the 5-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
74
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 17 publications
13
74
3
Order By: Relevance
“…Our study showed that almost all patients exhibited the classical triad of TP symptoms. This finding was similar to that of Uba et al [22] where all patients manifested with the classical features of TP. Perhaps this could be attributed to late presentation of the patients at which time the clinical features were already well established.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed that almost all patients exhibited the classical triad of TP symptoms. This finding was similar to that of Uba et al [22] where all patients manifested with the classical features of TP. Perhaps this could be attributed to late presentation of the patients at which time the clinical features were already well established.…”
Section: Discussionsupporting
confidence: 92%
“…The pathophysiology of anaemia is said to be multifactorial and includes bone marrow suppression, haemophagocytosis, sepsis and malnutrition [11,17] . Similar to many other reports [5,17,[22][23], the majority of perforations were singular in both genders. Our findings, in agreement with those of the Zaria series [5], showed that the perforation rate increased with age, though there was no significant statistical difference following this observation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, a number of hospital-based surveillance and case reports from several African countries suggests that typhoid is indeed a major public health concern, especially among school-age children. An earlier incidence study in Mali by Ferreccio et al [4] confirmed that S. Typhi and S. Paratyphi A were major causes of bacteremia among children younger than 2 years of age, while in Nigeria cases of ileal perforation due to typhoid were common in children younger than 5 years of age [5]. A breakdown in the portable water system in a South African suburb caused an outbreak of typhoid , causing illness in nearly 4,000 persons as well as several deaths [6].…”
Section: Introductionmentioning
confidence: 93%